THROMBOLYTIC AND ANTICOAGULANT THERAPY FOR PULMONARY EMBOLISM WITH HIGH AND INTERMENDIATE RISK OF EARLY DEATH. PART 1. MORTALITY ANDCOMPLICATIONS - O. V. Nikitina; I. P. Mikhailov; D. A. Kosolapov; V. I. Avfukov; E. A. Ostrogina; S. N. Kuznetsov; T. N. Cherkashina; N. I. Mirda (Неотложная медицинская помощь)
Background The advantages of thrombolytic therapy over anticoagulant therapy in the treatment of acute pulmonary embolism are uncertain. Aim of study To compare primary outcomes and incidence of complications in patients with PE of high and intermediate risk in the course of TLT or ACT and to assess efficacy and safety of TLT and ACT. Study Design Prospective non-randomized study. Intervention was administration of a thrombolytic, the control group consisted of patients who had an anticoagulant introduced. Characteristics of a sample 503 patients with a high and intermediate risk of early death at the age of 16 to 93 years (mean age 61±16, Ме 63 (51; 74) admitted to the resuscitation department in 2011–2016. Thrombolytics were administered to 222 patients, heparin — 281. Results The mortality rate was 10.8% (24/222) when treated with thrombolytic vs. 17.8% (50/281) with anticoagulant treatment; odds ratio was 0.56, 95% confidence interval 0.32; 0.97; p=0.031; P=0.60. The mortality rate in the subgroup with unstable hemodynamics was 30.2% (19/63) with thrombolytics vs. 47.1% (32/68) with anticoagulant treatment; OR 0.49 (0.22; 1.06); p=0.051; P=0.51. The mortality rate in the subgroup of intermediate risk was 3.2% (5/158) vs. 8.4% (18/214); OR 0.36 (0.11; 1.05); p=0.049; P=0.54. The use of thrombolytic was associated with a decrease in mortality: in the age group< 75 (mortality rate 5.5% (10/181) vs. 16.2% (33/204), OR 0.30 (0.14; 0.67); p=0.001, P=0.92); in the subgroup with acute cardiac arrhythmias (mortality rate 4.5% (1/122) vs. 44.0% (11/25); OR 0.061 (0.003; 0.557); p=0.002; P=0.91); in the subgroup with no hospital recurrence of embolism (mortality rate 1.6% (3/188) vs. 12.9% (32/248); OR 0.14 (0.03; 0.46), p< 0.001; P=1.0). With thrombolysis, infarction pneumonia developed less often: in 19.8% (44/222) vs. 28.8% (81/281); OR 0.61 (0.39; 0.95); p=0.022; P=0.64. There were no differences in the incidence of hemorrhagic complications in the treatment of thrombolytics in comparison with anticoagulant therapy: 7.7% (17/222) vs. 10.3% (29/281); OR 0.72 (0.37; 1.40); p=0.35; P=0.17. Severe hemorrhages (including intracranial): 2.7% (6/22) vs. 3.2% (9/281); OR 0.84 (0.26; 2.62); p=0.80; P=0.06. Minor hemorrhages: 5.0% (11/ 222) vs. 7.1% (20/281); OR 0.72 (0.31; 1.63); p=0.36; P=0.16. Intracranial hemorrhages: 0.90% (2/222) vs. 0.71% (2/281); OR 1.27 (0.13; 12.67); p=0.81; P=0.13). There was no difference in the re-occurrence of embolisms: 15.3% (34/222) and 11.7% (33/281); OR 1.36 (0.79; 2.35); p=0.29; P=0.22. Conclusion Thrombolytic therapy appeared to be more effective for survival compared to anticoagulant therapy with no differences in the incidence of complications.